2013
DOI: 10.1088/0004-637x/776/2/86
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Binary-Induced Spiral From an Incomplete Ring Pattern of Cit 6

Abstract: With the advent of high-resolution high-sensitivity observations, spiral patterns have been revealed around several asymptotic giant branch (AGB) stars. Such patterns can provide possible evidence for the existence of central binary stars embedded in outflowing circumstellar envelopes. Here, we suggest the viability of explaining the previously observed incomplete ring-like patterns with the spiral-shell structure due to the motion of (unknown) binary components viewed at an inclination with respect to the orb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 48 publications
6
63
0
Order By: Relevance
“…High-resolution imaging of a few dusty AGB stars reveals bipolar or more complex, clumpy structures (e.g., Weigelt et al 1998;Monnier et al 2000;Hofmann et al 2001). Some AGB stars show spiral structures, which strongly suggests the influence of a companion (e.g., Mauron & Huggins 2006;Maercker et al 2012;Kim et al 2013;Ramstedt et al 2014;Mayer et al 2014;Decin et al 2015). These observations suggest that the seed of the morphological change already exists in the AGB phase.…”
Section: Introductionmentioning
confidence: 92%
“…High-resolution imaging of a few dusty AGB stars reveals bipolar or more complex, clumpy structures (e.g., Weigelt et al 1998;Monnier et al 2000;Hofmann et al 2001). Some AGB stars show spiral structures, which strongly suggests the influence of a companion (e.g., Mauron & Huggins 2006;Maercker et al 2012;Kim et al 2013;Ramstedt et al 2014;Mayer et al 2014;Decin et al 2015). These observations suggest that the seed of the morphological change already exists in the AGB phase.…”
Section: Introductionmentioning
confidence: 92%
“…As a consequence, spirals can often be seen instead as concentric arcs. Ways to derive properties of the binary system based on the CSE morphology are discussed in Huggins et al (2009), Kim and Taam (2012c), and Kim et al (2013), and interpretations of observed morphologies through hydrodynamical simulations can be found in, e.g., Maercker et al (2012) and Kim et al (2017), Fig. 21, right panel.…”
Section: Impacts Of Companions On Cse Morphologymentioning
confidence: 99%
“…Bowers & Johnston 1990), spirals (e.g. Mauron & Huggins 2006;Mayer et al 2011;Maercker et al 2012;Kim et al 2013), tori (e.g. Skinner et al 1998), and bubbles .…”
Section: Introductionmentioning
confidence: 99%